UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROJECT BASED LEARNING SISWA KELAS IV SD NEGERI NO. 62/VI BEDENG REJO - Albahrul; Yohanes; Ferinaldi (Hiradika | Hira Institute, 2025)
This research is motivated by the low mathematics learning outcomes caused by the lack of student motivation in learning and teachers are still focused on the one-way learning process. The researcher offers a Project Based Learning model solution that leads to student and teacher creativity. The purpose of the study is to describe efforts to improve mathematics learning outcomes using the Project Based Learning model through classroom action research carried out in 3 cycles. The data obtained in this study are student learning outcomes through tests, and student activities during the learning process through observation sheets. The results of the study showed that the results of the cycle I test, the average student score was 61.54 with classical completeness of 46.15%, in the cycle II test results with an average score of 70.77 with classical completeness of 69.23% increased in cycle II and in cycle III the average student score was 76.15 with classical completeness of 80.77% increased from the previous cycle. Regarding the results of student observations in cycle I, the results were 65.88%, increasing to 75.89% in cycle II and becoming 80% in cycle III. It can be concluded that using the project-based learning model can improve the mathematics learning outcomes of grade IV students of SD Negeri No. 62/VI Bedeng Rejo in the 2024/2025 Academic Year.